Late Holocene paleovegetation and fire history of Northern Lake of the Woods and the Woodland Period - Birch, Kira (My University, 2023)
This thesis analyzes two Late Holocene lake sediment cores which were collected from the vicinity of two archaeological sites in northeastern Lake of the Woods, Ontario: the Bundoran Site (DjKn-5) and the Bud Site (DjKn-6). One of these cores was collected from a small pond between these sites and the other core was collected from the middle of a large bay in Lake of the Woods northwest of the sites. Both cores contain roughly 2000 years of sedimentation and the charcoal and pollen content are used to reconstruct local- and regionalscale vegetation history, changes in fire history, and the possibility of human impacts on vegetation during this period within the study area. The pollen sequences from both cores revealed the presence of a persistent pine-dominated forest environment, however the Bundoran Pond core showed greater levels of pollen loading from grasses, likely as a result of the differences in basin size between the pond and the bay. The pollen and charcoal sequences in the Route Bay core showed evidence of disturbance towards the top of the core that was not seen at Bundoran Pond. This is interpreted as representing a period of vegetation disturbance in the wider Lake of the Woods basin, but one of vegetation continuity surrounding the pond. The Bundoran Pond core also consistently contained charcoal fragments larger than 100 µm2, something which was not seen in the Route Bay core. This is interpreted as possibly representing anthropogenic burning near the pond. The Route Bay core contained a maize (Zea mays) pollen grain in its basal interval (70-72cm below surface), which had an associated radiocarbon date of 2120 ± 30 14C years BP (195 BCE to 105 BCE). This maize pollen grain provides the first definitive evidence of precontact maize cultivation in the Lake of the Woods region.